Exploring the Efficacy of Vocational Training Programs in Motor Vehicle and Mechanic Works Trade: A Case Study of Science and Technical Colleges in Northeast Nigeria - Sule, Samaila Yerima; Lare, Ojo Joshua; Oguntokun, John Ebenezer (International Journal of Education, Management, and Technology, 2024)
This study aimed to explore the efficacy of vocational training programs in Motor Vehicle and Mechanic Works Trade: a case study of science and technical colleges in northeast Nigeria. The study adopted a survey research design and was carried out in northeast Nigeria. The Zone includes the states of Adamawa, Bauchi, Borno, Gombe, Taraba, and Yobe, and is situated at latitude 6.260 East and longitude 4.920 North East of Nigeria. The population of the study was 621 comprising 128 MVMW trade teachers, 126 administrators (Principals and two Vice Principals), and 367 students from the 42 science and technical colleges in Northeast Nigeria. The study adopted Simple random sampling to select a sample size of 234 respondents using Krejcie and Morgan (1970) sample size table. The instrument for data collection was a structured questionnaire titled: “Efficacy of Vocational Training Programs in Motor Vehicle and Mechanic Works Trade Questionnaire, (EVTPMVMWTQ)". The data for the study was analyzed using mean and standard deviation to answer the research questions. The findings of the study revealed that the curriculum adequately covers essential topics, practical training facilities are well-equipped, instructors demonstrate expertise, safety protocols are emphasized, and opportunities for hands-on experience are provided. The findings further revealed that the high agreement levels, with mean scores above 4.0, across various aspects of the training program in Motor Vehicle and Mechanic Works (MVMW), suggest a positive perception among students regarding the effectiveness of the program. It was recommended that the government should upgrade and provide modern automotive equipment and tools to ensure vocational training programs have access to current resources. Collaborate with industry partners to facilitate equipment provision and ensure practical training aligns with industry standards.